Merce Cunningham after the arbitrary - Noland, Carrie 1958- (The University of Chicago Press, 2019)
Recycling the readymade : Marcel Duchamp and the rendez-vous in walkaround time -- Summerspace : the body in writing -- Nine permanent emotions and sixteen dances : drama in Cunningham -- "Passion in slow motion" : Suite for five and the photographic impulse -- Bound and unbound : the reconstruction of Crises -- The ethnics of vaudeville, the rhythms of Roaratorio -- Buddhism in the theatre
Includes bibliographical references and index
Keywords: Cunningham, Merce -- 1919-2009; Modern Dance; Cunningham, Merce / Criticism and interpretation; Cunningham, Merce / Sources; Modern dance / United States; Choreography